Dissemination of Indonesian Nasionalism and Islamic Religiosity Trough Podcast - Wibowo, Bunga Melanie; Ramadhani, Elsa; Putri, Dwi Helena; Wati, Lowfi Lidiya; Farhati, Nalal Muna; Yuliyanti, Najwa Putri; Zahra, Annisa Nuruz; Syafia, Abdil Aleema Dara (International Tatho Academics, 2025)
This study aims to identify and explore the values of Pancasila in the content of Habib Jafar’s podcast on Deddy Corbuzier’s Youtube channel. The qualitative study uses a media observation study approach. The subject matter in this study uses Pancasila values as the theory of analysis. The research data was obtained through documentation techniques. As for data analysis, it is obtained through the stages of data reduction, presentation and verification. This study confirms the existence of dimensions of Pancasila values in the content of Habib Jafar’s podcast, including the value of divinity in building tolerant religious awareness, the value of humanity in realizing a harmonious life, and the value of unity in strengthening diversity. The findings of this study confirm that there is a relationship between Islam and statehood in building the social life of Indonesian people who are tolerant in religion and state. The shortcomings of this study do not know the impact of podcast content on audiences, such as changes in attitudes that are in accordance with the values of Pancasila.